THE DOWNSIDE RISK OPTIMAL PORTFOLIO SELECTION PROBLEM - Anton Abdulbasah kamil et al. (Proceedings of ICMSA, 2005)
One of the basic problems of applied finance is the optimal selection ofstocks, with the aim of maximizing future returns and minimizing therisk using a specified risk aversion factor. Variance is used as the riskmeasure in classical Markowitz model, thus resulting in a quadraticprograrnming. As an altemative, mean absolute deviation was proposedas a risk measure to replace the original risk measure, variance. Thisproblem is a straight-forward extension of the classic Markowitz mean-varianceapproach and the optimal portfolio problem can be formulatedas a linear programming problem. Taking the downside risk as the riskleads to different optimal portfolio. The effect of using only downsiderisk on optimal portfolio is analyzed in this paper by taking the meanabsolute negative deviation as the risk measure. This method isapplied to the opimal selection of stocks listed in Bursa Malaysia andthe return of the optimal portfolio is compared to the classicalMarkowitz model and mean absolute deviation model. The result showthat the optimal portfolios using downside risk measure outperforms theother two models.Keywords;-Portfolio optimizatiorr, Linear Programming, Downside risk.